2019
DOI: 10.1111/jpn.13071
|View full text |Cite
|
Sign up to set email alerts
|

Spray‐dried porcine plasma improves feed intake of weaned piglets subjected to heat stress

Abstract: The objective of this study was to evaluate the effects of spray‐dried porcine plasma (SDPP) on performance, measurement of thyroid hormones triiodothyronine (T3) and thyroxine (T4), body temperature and relative organ weights of weaned piglets exposed to a heat stress or a thermoneutral environment. One hundred and forty‐four piglets with initial BW of 5.82 ± 0.33 kg (28 d old) were used. The experimental design was a 4 x 2 factorial arrangement, four plasma levels (0.0, 2.5, 5.0 and 7.5%) and two environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
4
0
1
Order By: Relevance
“…The present study demonstrated that the shrimp feed supplemented with porcine SDP, especially at 3-6% of the diet, could improve the growth performance, survival, feed utilization, immune responses, and reduce the mortality caused by V. parahaemolyticus infection. The effective dose of SDP for improving the overall health status of the Pacific white shrimp was mainly in agreement with those reported in the pig studies (5-8% SDP) [7][8][9][10][11]. Multiple modes of action of SDP have been proposed.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study demonstrated that the shrimp feed supplemented with porcine SDP, especially at 3-6% of the diet, could improve the growth performance, survival, feed utilization, immune responses, and reduce the mortality caused by V. parahaemolyticus infection. The effective dose of SDP for improving the overall health status of the Pacific white shrimp was mainly in agreement with those reported in the pig studies (5-8% SDP) [7][8][9][10][11]. Multiple modes of action of SDP have been proposed.…”
Section: Discussionsupporting
confidence: 86%
“…This includes enhancing growth performance, nutrient utilization, and feed intake, suppressing inflammation and disease incidence, and influencing gut microbiota in a positive manner [3,4,6]. Supplementation of SDP in the feed at 5-8% of the diet (50-80 g/kg diet) for 14-35 days was reported to significantly enhance the body weight and feed intake of weaned pigs with or without bacterial challenge [7][8][9][10][11]. Thus, it has been proposed for use as a growth promoter in the livestock industry.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of intestinal barrier function has also been reported with the dietary supplementation of spray-dried chicken plasma in weaning piglets [ 25 ]. In another study, the significant physiological and performance parameters observed in pigs supplemented with SDP and subjected to heat stress were linked to the enhancement of gut barrier integrity, antioxidant activity, and immune modulation [ 26 ]. This is the first study confirming the reduction of FITC-d in the serum of SDP-supplemented heat stress chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Foi observado que dietas suplementadas com proteínas plasmáticas, como plasma sanguíneo ou concentrado de imunoglobulinas, podem prevenir alterações na estrutura do epitélio durante o processo inflamatório e melhorar a função de barreira da mucosa intestinal (Cerqueira et al, 2019).…”
Section: Plasma Sanguíneo Como Alternativa à Utilização De Antimicrobianosunclassified